THE QUALITATIVE STUDY ON THE ROLE OF TEACHERS IN SHAPING CHARACTER OF LEARNING DISCIPLINE FOR STUDENTS AT STATE ELEMENTARY SCHOOLS IN GRESIK REGENCY - Syamsi, Moh; Khamim, Nur (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
Learning discipline can also make children not underestimate a job, including in learning, be more responsible for themselves and dislike work that is delayed, especially in learning discipline. The role of a teacher to shape the character of learning discipline can all be seen through how a teacher arranges learning tools, and prepares all needs that can support the success of learning and the success of students. The role of teachers in classroom management can also be a strong factor in the formation of students' disciplinary character, because it can provide learning motivation to students This research is a qualitative research that uses observation, interview, and document methods as tools to obtain relevant and supporting data in this study. All efforts to collect data in this study have intensified the observation and interview methods. in several State Elementary Schools in Gresik district. Which found that teachers take steps by developing personality and fostering student ethics, so that with the steps that have been taken, the role of teachers as educators has been able to improve student discipline